Cardiopulmonary exercise testing with elastic resistance: A new reproducible proposal for determination of ventilatory thresholds and maximum oxygen consumption - Gasparini Neto, V. H.; Santos Neves, L. N.; Kalva-Filho, C. A.; Schwingel, P. A.; Leite, R. D.; Carletti, L. (Journal of Sports Science & Medicine, 2022)
To propose a new Cardiopulmonary Exercise Test with Elastic Resistance (CPxEL) and compare the physiological responses to conventional cardiopulmonary exercise test (CPx) performed on a treadmill. In addition, we tested the reproducibility of the CPxEL. Twenty-four physically active participants completed the CPx (first session) and CPxEL twice (second and third sessions) interspersed by seven days. A treadmill protocol with increments of 1km·h-1 every minute until exhaustion was used in CPx. The CPxEL consisted of performing alternating steps back-and-forth against an elastic resistance attached to a belt and an incremental protocol with 1 stage (S) per minute following a cadence of 200 bpm controlled by a metronome in an 8-stage rubber mat. First analysis: first ventilatory threshold (VT1) occurred at 69.7% and 75.3% of maximal heart rate (HRmax) and 53.5% and 65.7% of maximal oxygen consumption (V?O2max). Second VT (VT2) occurred at 93.3% and 96.8% of the HRmax and 87.0% and 96.9% of V?O2max for CPx and CPxEL, respectively. At exhaustion, V?O2max, perceived exertion (BORG-CR10 and OMNI-RES EB), and test duration presented lower values for CPxEL (P < 0.05). Second analysis: VT1 occurred at warm-up (S0) (P = 0.731), VT2 occurred at S5 (P = 0.912), and the exhaustion occurred at S6 and S7 (P = 0.271) for CPxEL and retest, respectively. The intraclass correlation coefficient (ICC) for V?O2max was 0.921 and for HRmax was 0.930. The CPxEL has good test-retest reproducibility and represents a possible and interesting add-on to determine maximal oxygen consumption, maximal heart rate, and second ventilatory threshold without using traditional ergometers.